VOIP AND THE FUTURE OF THE INTERNET (I) - Unger, Tomás (2001)
In 1997, data traffic over the telephone network in the U.S. surpassed that of voice. By then it was possible to send voice messages over the Internet. However, this was not as easy as it looked. A new generation of mobile technology and advances in Internet portend changes to alter their current risk free nature of universal network without controls.